WINDOWS 98 simplified :a step by step guide - Palani Murugappan (Vento, 1999)
[This book] covers topics on using the mouse, the various shortcut commands using the right mouse button, moving items in the Start menu, customising your desktop screen, multimedia, and using the system tools.